ANALISIS IKLAN MIE SEDAAP TASTY BEEF YAKINIKU DITINJAU DARI ETIKA PARIWARA INDONESIA (EPI) - Prasetyo Dwi Apanca; Brilliant Naufal Muhammad; Muchamad Vanza Arjuna; Daniel Handoko (CV. Denasya Smart Publisher, 2025)
An This study aims to analyze the advertisement of Mie Sedaap Tasty Beef Yakiniku reviewed from the perspective of Indonesian Advertising Ethics. Instant food advertisements are often packaged creatively and persuasively, but often violate advertising norms and ethics. This study uses a descriptive qualitative approach with a content analysis method. The results of the study indicate that several elements in this advertisement violate the principles of honesty and social responsibility as stated in the Indonesian Advertising Ethics, especially in terms of taste claims, visualization of ingredients, and excessive depictions of deliciousness. This study recommends that advertisers pay more attention to ethical standards so as not to mislead consumers.